Model Pembentukan Peraturan Perundang-Undangan Pasca Putusan Mahkamah Konstitusi Nomor 91/Puu-Xviii/2020 - Tibaka, Leli; Primayanti, Andi Dewi; Chalid, Idham; S, Irzha Friskanov. (Res Judicata, 2023)
In actuality, the Constitutional Court's decision confirms that the Job Creation Law's formation is conditionally illegal, which means that the methods, strategies, and procedures used to create the Job Creation Law are against the Constitution. Given that article 22A of the constitution states that "Further provisions regarding the procedures for forming laws are regulated by law," this demonstrates to the public that there is a problem with legislators (the DPR and the President) disobeying the Guidelines for Forming Laws and Regulations. Because its text is a direct order from Article 22A of the Republic of Indonesia's 1945 Constitution, the law in question, Law Number 12 of 2011, is substantively and materially the same as the Constitution. The issue is how the decision will be positioned and what its repercussions will be. utilizing legislative methodologies and normative research techniques. The findings demonstrate that court rulings actually produce legal clarity and represent justice, and demonstrate that some of the aforementioned provisions are the foundation for existence